Pengaruh Variasi Volume Konsentrasi Bakteri Bacillus Subtilis Terhadap Sifat Fisik Beton - Fajar Priandoko; Zulfikar Djauhari; Enno Yuniarto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In general, construction in Indonesia still uses concrete as a building material. It is proven by more than 60% of projects in Indonesia were using concrete as its construction material. Starts from the simplest constructions to the complex technology projects, concrete becomes an inevitable need. Concrete has several advantages and disadvantages. The problem that often occurs in concrete is it can crack either due to physical changes from the concrete itself or external influences. One way to solve this problem is to use the Bacillus Subtilis bacterium as a concrete mixture. This bacterium is capable of repairing cracks in concrete. That is why this research will use BacillusSubtilis bacteria with different variations in volume concentration, it will be 105 cells / 20 ml, 105 cells / 25 ml and 105 cells / 30 ml as much as 25 ml in castings of 0.1 m3. This research will investigate the physical properties of concrete, which are workability, porosity, and shrinkage of concrete. The test objects are cylindrical and soaked in normal water for 28 days and 56 days. The workability test results showed the highest slump value obtained in bacterial concrete with a concentration of 105 cells / 30 ml with a slumpvalue of 12 cm. The lowest porosity values of 28 and 56 days ages were obtained in bacterial concrete concentrations of 105 cells / 20 ml with porosity values of 12.83% and 10.31%, respectively. The concrete bacteria concentration of 105 cells / 20 ml also has the smallest shrinkage value of 0.064 mm. The addition of Bacillus Subtilis bacteria witha concentration of 105 cells / 20 ml was the most optimal of all variations of theconcentration used to the physical properties test of concrete.Keywords: Concrete, Volume Concentration, Bacillus Subtilis, Physical Properties